2010
DOI: 10.2514/1.41352
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a High-Frequency Pulsed-Plasma Jet Actuator for Supersonic Flow Control

Abstract: An experimental study is conducted to characterize the performance of a pulsed-plasma jet (called a "spark jet" by other researchers) for potential use in supersonic flow control applications. A pulsed-plasma jet is a high-speed synthetic jet that is generated by striking an electrical discharge in a small cavity. The gas in the cavity pressurizes owing to the heating and is allowed to escape through a small orifice. To obtain an estimate of the relative strength of the pulsed-plasma jet, the jet is injected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(87 citation statements)
references
References 32 publications
2
84
0
1
Order By: Relevance
“…This actuator is able to produce high-speed jet velocities, with a peak velocity measured by the PIV technique in excess of 50 m/s [13]. A pulsed plasma jet inspired by the sparkjet actuator is presented in [14], with a jet velocity of the order of 300 m/s. The ONERA, in collaboration with the CNRS Laplace laboratory (France), is also involved in research into a PSJ actuator [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This actuator is able to produce high-speed jet velocities, with a peak velocity measured by the PIV technique in excess of 50 m/s [13]. A pulsed plasma jet inspired by the sparkjet actuator is presented in [14], with a jet velocity of the order of 300 m/s. The ONERA, in collaboration with the CNRS Laplace laboratory (France), is also involved in research into a PSJ actuator [15].…”
mentioning
confidence: 99%
“…In recent years, various studies have been conducted on electrostatic and electromagnetic actuators. Actuators making use of piezoelectric materials [1][2][3] or plasma [4][5][6][7][8][9][10][11][12][13][14][15] are also being developed. There are several possible configurations for piezoelectric actuators, including: a synthetic jet [1][2] and a flat plat actuator [3].…”
mentioning
confidence: 99%
“…Narayanaswamy et al 83 also observed that there is a limit on the frequency used due to the actuator beginning to miss pulses at higher values. The geometric features examined by Sary et al 80 were the neck radius i.e.…”
Section: Pulsed Plasma Synthetic Jetsmentioning
confidence: 99%
“…It has been noted that, with continuous use, increasing temperatures can slow the refill time of the actuator cavity and thus place an upper limit on the operating frequency. 80,83 Depending on the scenario, higher frequencies may be a necessity for future applications e.g. position control of oscillating shock waves in high speed intakes.…”
Section: Future Work On Pulsed Plasma Synthetic Jetsmentioning
confidence: 99%
“…Explanations of these steps will be comprehensively explained in the section 2. Narayanaswamy et al [6] carried out the experimental study via PSJ actuator having different cavity volume and orifice diameter. They had measured temperature of actuator by using optical emission spectroscopy and also obtained jet exit velocity of about 250 m/s with consuming discharge energies of about 35 mJ per generated jet.…”
Section: Introductionmentioning
confidence: 99%